Green human resource management –unveiling the emerging themes and scopes for further studies - Habtoosh, Eman; Mohamed, Rosmah; Ali, Mass Hariza; Ismail, Noor Azlin (Penerbit Kolej Universiti Islam Antarabangsa Selangor, 2024)
Green human resource management has recently caught the attention of researchers due to global environmental concerns thus sustainable development. Accordingly, academic researchers have been enormously focusing on this particular domain. As a result, it is deemed acknowledged research trends and themes are rising in this domain. Therefore, it is indeed crucial to explore the research trends in this particular topic to allow future researchers to find scopes for further study. Consequently, this study aims to explore the research publication trend, themes, and scopes for further study. To achieve this objective, both Scopus and the Web of Science databases were used to gauge the research publications relevant to green human resource management. A total refined of 396 documents were taken to perform bibliometric analysis. The findings showed a gradual growth in the publication in recent years at a significant pace. Furthermore, mainly three themes were observed namely, green human resource management linked to environmental management and green behavior, sustainability and performance, and green innovation and green intellectual capital. These findings enable future researchers to learn the existing themes that have already been emphasized which creates new opportunities for future studies. Policymakers may find these findings crucial to observe the current role of human resource management from different sectors which allow them to support further studies for robust output.